Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jürgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kühn, Tilman; et al. (European Journal of Nutrition)
Abstract Purpose The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Multi-Objective Trust-Region Filter Method for Nonlinear Constraints using Inexact Gradients - Berkemeier, Manuel Bastian; Peitz, Sebastian (arXiv:2208.12094)
In this article, we build on previous work to present an optimization algorithm for nonlinearly constrained multi-objective optimization problems. The algorithm combines a surrogate-assisted derivative-free trust-region approach with the filter method known from single-objective optimization. Instead of the true objective and constraint functions, so-called fully linear models are employed and we show how to deal with the gradient inexactness in the composite step setting, adapted from single-objective optimization as well. Under standard assumptions, we prove convergence of a subset of iterates to a quasi-stationary point and if constraint qualifications hold, then the limit point is also a KKT-point of the multi-objective problem.

Brief Announcement: The (Limited) Power of Multiple Identities: Asynchronous Byzantine Reliable Broadcast with Improved Resilience through Collusion - Götte, Thorsten; Scheideler, Christian (SPAA ’22: 34th ACM Symposium on Parallelism in Algorithms and Architectures, Philadelphia, PA, USA, July 11 - 14, 2022)

Decision Support Ecosystems: Deﬁnition and Platform Architecture - Kirchhoff, Jonas; Weskamp, Christoph; Engels, Gregor (Decision Support Systems XII: Decision Support Addressing Modern Industry, Business, and Societal Needs)
Decision support systems are crucial in helping decision makers to quickly identify optimal business decisions in increasingly volatile and complex business environments. However, the ideal DSS for one decision maker may not optimally address the requirements for decision support of another decision maker. This is due to differences between decision makers in business goals, regulatory restrictions or availability of resources such as data. By using a suboptimal DSS, decision makers risk implementing suboptimal decision recommendations which endanger the success of their business. This presents DSS developers with the challenge to implement a customizable DSS which can be tailored to the individual requirements for decision support of a single decision maker. In order to address this challenge, we suggest a decision support ecosystem in which DSS developers, decision makers and other domain experts collaborate using a shared platform to provide and combine reusable decision support services into a tailored DSS. The contribution of our paper is twofold: First, we define the concept of a decision support ecosystem with respect to existing digital business ecosystems and discuss expected benefits and challenges. Second, we present a reference architecture for a shared platform supporting the realization of a decision support ecosystem. We demonstrate our contributions in the example application domain of regional energy distribution network planning.

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))
In this work, methods will be evaluated to numerically calculate the passive electrical parameters of planar coils. These parameters can then be used to optimize inductive applications such as wireless power transmission. The focus here will be on inductive localization, which uses high-frequency magnetic fields and the resulting induced voltage to provide localization through the coupling parameter mutual inductance. To achieve localization with high accuracy and best possible operation (resonance, signal strength, etc.), the coil parameters need to be well known. For this reason, some numerical methods for the calculation of these quantities are presented and validated. In addition, the physical effects are thereby considered in more detail, allowing the localization procedure to be better optimized compared to simulative black-box methods. The goal should be a dedicated simulation platform for planar coils to be able to develop training data for neural networks and to test and optimize localization algorithms.
Keywords: Simulation Environment; Inductive Localization; Coil Parameters; Inductive Applications; Near-Field

On the Role of Hydrogen Bond Strength and Charge Transfer of a Diels-Alder Reaction On-Water: Semiempirical and Free Energy Calculations. - Henao Aristizabal, Andres; Gohar, Yomna; Whilhelm, René; Kühne, Thomas
Accelerated chemistry at the interface with water has received increasing attention. The mechanisms behind the enhanced reactivity On-Water are not yet clear. In this work we use a Langevin scheme in the spirit of second generation Car-Parrinello to accelerate the second-order density functional Tight-Binding (DFTB2) method in order to investigate the free energy of two Diels-Alder reaction On-Water: the cycloaddition between cyclopentadiene and ethyl cinnamate or thionocinnamate. The only difference between the reactants is the substitution of a carbonyl oxygen for a thiocarbonyl sulfur, making possible the distinction between them as strong and weak hydrogen-bond acceptors. We find a different mechanism for the reaction during the transition states and uncover the role of hydrogen bonds along with the reaction path. Our results suggest that acceleration of Diels-Alder reactions do not arise from an increased number of hydrogen bonds at the transition state and charge transfer plays a significant role. However, the presence of water and hydrogen-bonds is determinant for the catalysis of these reactions.

Collaborative Modeling of Use Case & Damage Scenarios in Online Workshops Using a 3D Environment - Japs, Sergej; Schmidt, Sebastian; Kargl, Frank; Kaiser, Lydia; Kharatyan, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The development of technical systems requires close cooperation of stakeholders from different disciplines. This collaboration takes place in workshops. Driven by digitalization and by the current pandemic such workshops take place primarily online. Suitable collaboration tools and methods are crucial to success. At the beginning of such workshops, use and damage scenarios are identified. In this paper, we presented a method and tool for identifying and modeling use and damage scenarios, which we evaluated in 14 online workshops with a total of 118 participants over a period of almost 3 years.

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, C. R.; Böhnke, M.; Bobbert, M.; Meschut, G. (The Minerals, Metals & Materials Series)

2022 Edsger W. Dijkstra Prize in Distributed Computing - Aguiliera, Marcos; Richa, Andréa W.; Schwarzmann, Alexander A.; Panconesi, Alessandro; Scheideler, Christian; Woelfel, Philipp (PODC ’22: ACM Symposium on Principles of Distributed Computing, Salerno, Italy, July 25 - 29, 2022)

A Data Driven Modelling Approach for the Strain Rate Dependent 3D Shear Deformation and Failure of Thermoplastic Fibre Reinforced Composites: Experimental Characterisation and Deriving Modelling Parameters - Gerritzen, Johannes; Hornig, Andreas; Gröger, Benjamin; Gude, Maik (Journal of Composites Science)
The 3D shear deformation and failure behaviour of a glass fibre reinforced polypropylene in a shear strain rate range of γ˙=2.2×10−4 to 3.4 1s is investigated. An Iosipescu testing setup on a servo-hydraulic high speed testing unit is used to experimentally characterise the in-plane and out-of-plane behaviour utilising three specimen configurations (12-, 13- and 31-direction). The experimental procedure as well as the testing results are presented and discussed. The measured shear stress–shear strain relations indicate a highly nonlinear behaviour and a distinct rate dependency. Two methods are investigated to derive according material characteristics: a classical engineering approach based on moduli and strengths and a data driven approach based on the curve progression. In all cases a Johnson–Cook based formulation is used to describe rate dependency. The analysis methodologies as well as the derived model parameters are described and discussed in detail. It is shown that a phenomenologically enhanced regression can be used to obtain material characteristics for a generalising constitutive model based on the data driven approach.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Dimensionierung und Optimierung von im FDM-Verfahren 3D-gedruckten Direktverschraubungen aus ABS - Moritzer, Elmar; Held, Christian; Hillemeyer, Johannes (Joining Plastic)

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

Can Machine Translation be a Reasonable Alternative for Multilingual Question Answering Systems over Knowledge Graphs? - Perevalov, Aleksandr; Both, Andreas; Diefenbach, Dennis; Ngonga Ngomo, Axel-Cyrille (WWW ’22: The ACM Web Conference 2022, Virtual Event, Lyon, France, April 25 - 29, 2022)

Kronecker Decomposition for Knowledge Graph Embeddings - Demir, Caglar; Lienen, Julian; Ngonga Ngomo, Axel-Cyrille (HT ’22: 33rd ACM Conference on Hypertext and Social Media, Barcelona, Spain, 28 June 2022- 1 July 2022)

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

On non-extinction in a Fleming-Viot-type particle model with Bessel drift - Kolb, Martin; Liesenfeld, Matthias (Electronic Journal of Probability)
Motivated by the work [6] of Mariusz Bieniek, Krzysztof Burdzy and Soumik Pal we study a Fleming-Viot-type particle system consisting of independently moving particles each driven by generalized Bessel processes on the positive real line. Upon hitting the boundary {0} this particle is killed and an uniformly chosen different one branches into two particles. Using the symmetry of the model and the self similarity property of Bessel processes, we obtain a criterion to decide whether the particles converge to the origin at a finite time. This addresses open problem 1.4 in [6]. Specifically, inspired by [6, Open Problem 1.5], we investigate the case of three moving particles and refine the general result of [6, Theorem 1.1(ii)] extending the regime of drift parameters, where convergence does not occur – even to values, where it does occur when considering the case of only two particles.

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Flexible Time-Domain De-Multiplexing of Nyquist OTDM Channels by Orthogonal Sampling in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Conference on Lasers and Electro-Optics)
We report for the first time, inter-symbol-interference (ISI) free demultiplexing of Nyquist optical time division multiplexed (OTDM) signals using a reconfigurable orthogonal sinc-pulse sampling enabled by silicon photonic Mach-Zehnder Modulators.

Wideband SiN pulse interleaver for optically-enabled analog-to-digital conversion: a device-to-system analysis with cyclic equalization - Zazzi, Andrea; Müller, Juliana; Ghannam, Ibrahim; Battermann, Moritz; Rajeswari, Gayatri Vasudevan; Weizel, Maxim; Scheytt, J. Christoph; Witzens, Jeremy (Optics Express)
We present the design and experimental characterization of a silicon nitride pulse interleaver based on coupled resonator optical waveguide filters. In order to achieve a targeted free spectral range of 1.44 THz, which is large given the reduced optical confinement of the silicon nitride platform, individual ring resonators are designed with tapered waveguides. Its application to time-interleaved photonically-assisted ADCs is analyzed by combining experimental characterization of the photonic integrated circuit with a comprehensive model of the entire ADC. The impact of fundamental signal distortion and noise sources affecting the converter is investigated and suitable equalization techniques at the digital signal processing level are evaluated. The novel application of a simple but powerful equalization filter in the DSP domain allows for a significant improvement of the digitized signal SNR. An ENOB of 5 over a 75 GHz bandwidth (150 GS/s) and an ENOB of 4.3 over a 100 GHz bandwidth (200 GS/s) are expected to be achievable with compact and off-the-shelf single-section semiconductor mode locked lasers, that can be further improved with lower noise light sources.

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Neuronale Netze in der Konstruktion zur Ausschöpfung der Potentiale additiver Fertigungstechnologien - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Bericht 407 - 7. Tagung des DVM-Arbeitskreises Additiv gefertigte Bauteile und Strukturen)
Die additive Fertigung bietet die Möglichkeit, digitale Prototypen dank der Besonderheit der werkzeuglosen Fertigung schnellstmöglich in reale Strukturen umzusetzen. Dieses Verfahren kann jedoch nur dann mit optimaler Geschwindigkeit genutzt werden, wenn Engpässe wirksam vermieden werden können. Einer dieser Engpässe ist der Konstruktionsprozess. Gerade im Bereich der additiven Fertigung sind in letzter Zeit immer leistungsfähigere Softwarelösungen erschienen, die das Design für die additive Fertigung, einschließlich der meisten Computer-Aided-Design (CAD)-Aufgaben, beschleunigen. In vielen Bereichen wird daher bereits versucht, so viele Schritte wie möglich zu automatisieren, nicht selten unter Verwendung neuronaler Netze und künstlicher Intelligenz. Dieser Beitrag zeigt am Beispiel einer automatisierten Strukturoptimierung eines Stuhls, warum das Nutzen neuronaler Netze im Konstruktionsprozess sinnvoll ist, um die Bereiche der konventionellen Topologieoptimierung und des Generative Design weiter zu verknüpfen und somit die Produktentwicklungszeit zu reduzieren.
Keywords: Künstliche Intelligenz; Neuronale Netze; 3D-Druck; Design for Additive Manufacturing

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Effects of Digital Transformation on Job Satisfaction and Employee Retention: An Integrative Framework - Depenbusch, Sarah; Schürmann, Mirko; Schaper, Niclas; Seifert, Andreas; Schumacher, Jan-Philip; Straatmann, Tammo

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Torkaman, Najmeh Filvan; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

Methodenentwicklung zur numerischen Lebensdauerprognose von hyperelastischen Klebverbindungen infolge zyklischer Beanspruchung mittels bruchmechanischer Ansätze - Tews, Karina; Aubel, Tobias; Teutenberg, Dominik; Meschut, Gerson; Duffe, Tobias; Kullmer, Gunter (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Automated UX Evaluation for User-Centered Design of VR Interfaces - Karakaya, Kadiray; Yigitbas, Enes; Engels, Gregor (Proceedings of the 9th International Working Conference on Human-Centered Software Engineering (HCSE'22))

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung unter Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Golebiowska, Sandra; Rieker, Florian; Ebbert, Christoph; Grundmeier, Guido

Towards Situation-specific Software Support for Cross-organizational Design Thinking Processes - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 5th International Workshop on Software-intensive Business (IWSiB'22))
Due to the increasing influences of a VUCA world, design thinking workshops have been established as a standard technique to build solutions according to uncertain customer needs. Concerning the ongoing pandemic and rising development of solutions across organizations, more and more workshops were conducted online with software support. However, existing software tools insufficiently address the different workshop situations in terms of the process (i.e., fixed tasks to conduct), the place (e.g., static online whiteboards), and people (i.e., synchronous working of all stakeholders). Therefore, we propose a design science study to develop a situation-specific software support that can be configured with flexible development processes, different places, and task-related people. Based on practical experience in existing research projects, we derive the initial design requirements and map them to a set of design principles. Out of that, we design a concept with its implementation as a software tool and point out open challenges.
Keywords: design thinking; situation-specific; cross-organizational; software support

Comparative Evaluation of AR-based, VR-based, and Traditional Basic Life Support Training - Yigitbas, Enes; Krois, Sebastian; Renzelmann, Timo; Engels, Gregor (Proceedings of the 10th International Conference on Serious Games and Applications for Health (SeGAH'22))

Sozialistische Berufswahl und Nachwuchslenkung in der DDR - Heisler, Dietmar (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)
Der vorliegende Beitrag befasst sich mit der Berufswahl in der ehemaligen DDR. Hier wurde von einer "gelenkten Berufswahl" gesprochen. Dabei galten alle Berufe als gleichwertig. "Sozialistische Berufswahl" wurde als pädagogisches Programm und als freie Berufswahl betrachtet. Dies gilt es genauer zu erörtern. Grundlage sind Beiträge, die in der Berufsbildung zwischen 1950 und 1979 erschienen sind.
Keywords: Berufswahl; DDR

Electron polarons in lithium niobate: Charge localization, lattice deformation, and optical response - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (New Trends in Lithium Niobate: From Bulk to Nanocrystals)
Lithium niobate (LiNbO3), a material frequently used in optical applications, hosts different kinds of polarons that significantly affect many of its physical properties. In this study, a variety of electron polarons, namely free, bound, and bipolarons, are analyzed using first-principles calculations. We perform a full structural optimization based on density-functional theory for selected intrinsic defects with special attention to the role of symmetry-breaking distortions that lower the total energy. The cations hosting the various polarons relax to a different degree, with a larger relaxation corresponding to a larger gap between the defect level and the conduction-band edge. The projected density of states reveals that the polaron states are formerly empty Nb 4d states lowered into the band gap. Optical absorption spectra are derived within the independent-particle approximation, corrected by the GW approximation that yields a wider band gap and by including excitonic effects within the Bethe-Salpeter equation. Comparing the calculated spectra with the density of states, we find that the defect peak observed in the optical absorption stems from transitions between the defect level and a continuum of empty Nb 4d states. Signatures of polarons are further analyzed in the reflectivity and other experimentally measurable optical coefficients.

Bound polaron formation in lithium niobate from ab initio molecular dynamics - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Applied Physics A)
Abstract Polarons influence decisively the performance of lithium niobate for optical applications. In this work, the formation of (defect) bound polarons in lithium niobate is studied by ab initio molecular dynamics. The calculations show a broad scatter of polaron formation times. Rising temperature increases the share of trajectories with long formation times, which leads to an overall increase of the average formation time with temperature. However, even at elevated temperatures, the average formation time does not exceed the value of 100 femtoseconds, i.e., a value close to the time measured for free, i.e., self-trapped polarons. Analyzing individual trajectories, it is found that the time required for the structural relaxation of the polarons depends sensitively on the excitation of the lithium niobate high-frequency phonon modes and their phase relation.
Keywords: General Materials Science; General Chemistry

Further Development of an Adaptive Joining Technique Based on Friction Spinning to Produce Pre-Hole-Free Joints - Wischer, Christian; Homberg, Werner (Key Engineering Materials)
Mechanical joining processes are an essential part of modern lightweight construction. They permit materials of different types to be joined in a way that is suitable for the loads involved. These processes reach their limits, however, as soon as the boundary conditions change. In most cases, these elements are specially adapted to the joining point and cannot be used universally. Changes require cost-intensive adaptation of both the element and the process control, thus making production more complex. This results in high costs due to the increased number of auxiliary joining element variants required and reduces the economic efficiency of mechanical joining. One approach to overcoming this issue is the use of adaptive auxiliary joining elements formed by friction spinning. This article presents the current state of research on pre-hole-free joining with adaptive joining elements. The overall process chain is illustrated, explained and analyzed. Special attention is paid to demonstrating the feasibility of pre-hole-free joining with adaptive joining elements. The chosen mechanical parameters are subsequently listed. Finally, a comprehensive outlook of the future development potential is derived.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Methodenentwicklung zur Auslegung geklebter Verbindungen aus hochfestem Stahl unter Berücksichtigung betriebsrelevanter Beanspruchungen im Landmaschinen- und Anlagenbau - Göddecke, Johannes; Meschut, Gerson; Göhrs, Tim; Große Gehling, Manfred

UCAI 2022 - 3rd International Workshop on User-Centered Artificial Intelligence - Buschek, Daniel; Hauptmann, Hanna; Heuer, Hendrik; Loepp, Benedikt; Riener, Andreas; Yigitbas, Enes (Proceedings of the Mensch Und Computer 2022 (MuC ’22))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Boosting artificial intelligence in design processes by the use of additive manufacturing - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium 2022)
Additive manufacturing offers the option of converting digital prototypes into real structures as quickly as possible by the special property of tool-free manufacturing. However, this process can only be used at optimum speed if bottlenecks can be effectively avoided. One of these constraints is the design process. Although modern CAD systems allow a significant increase in many areas, this always requires a person with specific skills (e.g. engineer). In the field of AM in particular, more and more powerful software solutions have recently been published which accelerate the Design for Additive Manufacturing, including most CAD-tasks. In many areas, therefore, attempts are already made to automate relevant design steps as much as possible, more and more using neural networks and artificial intelligence. This paper presents how and why such techniques can be used to generate three-dimensional structures quickly and efficiently in cases of deep generative design tasks.

Experimental Demonstration of a 2.2kW Active-Clamp Converter for High-Current Wide-Voltage-Transfer Ratio Applications - Rehlaender, Philipp; Korthauer, Bastian; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Phase-Shift Modulation for Flying-Capacitor DC-DC Converters - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Analysis of the Segregation Phenomena of Wood Fiber Reinforced Plastics - Moritzer, Elmar; Flachmann, Felix; Richters, Maximilian; Neugebauer, Marcel (Journal of Composites Science)
Wood–plastic composites (WPC) are enjoying a steady increase in popularity. In addition to the extrusion of decking boards, the material is also used increasingly in injection molding. Depending on the formulation, geometry and process parameters, WPC tends to exhibit irregular filling behavior, similar to the processing of thermosets. In this work, the influence of matrix material and wood fiber content on the flow, mold filling and segregation behavior of WPC is analyzed. For this purpose, investigations were carried out on a flow spiral and a sheet cavity. WPC based on thermoplastic polyurethane (TPU) achieves significantly higher flow path lengths at a wood mass content of 30% than polypropylene (PP)-based WPC. The opposite behavior occurs at higher wood contents due to the different shear thinning behavior. Slightly decreased wood contents could be observed at the beginning of the flow path and greatly increased wood contents at the end of the flow path, compared to the starting material. When using the plate cavity, flow anomalies in the form of free jets occur as a function of the wood content, with TPU exhibiting the more critical behavior. The flow front is frayed, but in contrast to the flow spiral, no significant wood accumulation could be detected due to the shorter flow path lengths.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)
The application of the mechanical joining process clinching enables the joining of sheet metals with a wide range of material-thickness configurations, which is of interest in lightweight construction of multi-material structures. Each material-thickness combination results in a joint with its own property profile that is affected differently by variations. Manufacturing process-related effects from preforming steps influence the geometric shape of a clinched joint as well as its load-bearing capacity. During the clinching process high degrees of plastic strain, increased temperatures and high strain rates occur. In this context, a 3D numerical model was developed which can represent the material-specific behaviour during the process chain steps sheet metal forming, joining, and loading phase in order to achieve a high predictive accuracy of the simulation. Besides to the investigation of the prediction accuracy, the extent of the influence of individual modelling aspects such as temperature and strain rate dependency is examined.

An approach for an innovative 3d steel strip straightening machine for curvature and saber compensation - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Homberg, Werner; Trächtler, Ansgar
Due to increasing globalization and rising quality requirements, the steel and metal processing industry is facing growing cost and innovation pressure. Not least because of their high lightweight potential, high-strength steel materials are meeting the growing material requirements of steel and metal processing in areas such as aerospace and medical technology. In particular, the tight tolerance limits of applicable shape and dimensional accuracies pose a challenge in the processing of high-strength steel strip materials. Improving the processability of high-strength steel materials through the use of straighteners with set-up assistance systems significantly increases the potential for competing with other materials such as aluminum or magnesium alloys.

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas Markus; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Experimental Analysis of Residual Stresses in CFRPs through Hole-Drilling Method: The Role of Stacking Sequence, Thickness, and Defects - Wu, Tao; Kruse, Roland; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Lauhoff, Christian; Niendorf, Thomas (Journal of Composites Science)
Carbon fiber reinforced plastics (CFRPs) gained high interest in industrial applications because of their excellent strength and low specific weight. The stacking sequence of the unidirectional plies forming a CFRP laminate, and their thicknesses, primarily determine the mechanical performance. However, during manufacturing, defects, e.g., pores and residual stresses, are induced, both affecting the mechanical properties. The objective of the present work is to accurately measure residual stresses in CFRPs as well as to investigate the effects of stacking sequence, overall laminate thickness, and the presence of pores on the residual stress state. Residual stresses were measured through the incremental hole-drilling method (HDM). Adequate procedures have been applied to evaluate the residual stresses for orthotropic materials, including calculating the calibration coefficients through finite element analysis (FEA) based on stacking sequence, laminate thickness and mechanical properties. Using optical microscopy (OM) and computed tomography (CT), profound insights into the cross-sectional and three-dimensional microstructure, e.g., location and shape of process-induced pores, were obtained. This microstructural information allowed for a comprehensive understanding of the experimentally determined strain and stress results, particularly at the transition zone between the individual plies. The effect of pores on residual stresses was investigated by considering pores to calculate the calibration coefficients at a depth of 0.06 mm to 0.12 mm in the model and utilizing these results for residual stress evaluation. A maximum difference of 46% in stress between defect-free and porous material sample conditions was observed at a hole depth of 0.65 mm. The significance of employing correctly calculated coefficients for the residual stress evaluation is highlighted by mechanical validation tests.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Knowledge Annotation within Research Data Management System for Oxygen-Free Production Technologies - Mozgova, Iryna; Altun, Osman; Scheveleva, Tatyana; Castro, Andre; Oladazimi, Pooya; Koepler, Oliver; Lachmayer, Roland; Auer, Sören

DigiBody - Digitale Prozesskette zur Abbildung und Optimierung der Fügetechnik im Rohbau - Jamei, Said; Döller, Norbert; Lossau, Sebastian; Beule, Felix; Al Trjman, Mohamad; Aubel, Tobias; Meschut, Gerson; Sommer, Daniel; Facciotto, Silvio; Droste, Alexander; Haufe, Andre; Helbig, Martin; et al. (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Model-driven Design and Management of Professional Education Programmes - Wolters, Dennis; Engels, Gregor (ICSOB'22 Companion Proceedings)

Increasing the Prediction Quality of Clinching Process Simulation with Extensible Die by Means of Friction Modeling as a Function of the Local Joining Process Parameters - Rossel, Moritz Sebastian; Meschut, Gerson

Zum Einstieg: Master-Arbeit zu ökologischer und sozial gerechter Stadtplanung. Ein fiktives Beispiel - Freymuth, Nina (Wissenschaftsläden in der Sozialen Arbeit. Partizipative Forschung und soziale Innovationen)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet’: results from a multistakeholder workshop - Vinoy, Sophie; Goletzke, Janina; Rakhshandehroo, Maryam; Schweitzer, Lisa; Flourakis, Matthieu; Körner, Antje; Alexy, Ute; van Schothorst, Evert M.; Ceriello, Antonio; Zakrzewski-Fruer, Julia K.; Buyken, Anette (European Journal of Nutrition)
Abstract To summarize current knowledge and gaps regarding the role of postprandial glycaemic response in the paediatric population, a workshop was organized in June 2021 by the European branch of the International Life Science Institute (ILSI). This virtual event comprised of talks given by experts followed by in-depth discussions in breakout sessions with workshop participants. The main pre-specified topics addressed by the workshop organizing committee to the invited speakers and the workshop participants were: (1) the role of glycaemic responses for paediatric health, based on mechanistic insights from animal and human data, and long-term evidence from observational and intervention studies in paediatric populations, and (2) changes in metabolism and changes in dietary needs from infancy to adolescence. Each talk as well as the discussions were summarised, including the main identified research gaps. The workshop led to the consensus on the crucial role on health of postprandial glycaemic response in paediatric population. However, a lack of scientific data has been identified regarding detailed glucose and insulin profiles in response to foods commonly consumed by paediatric populations, as well as a lack of long-term evidence including the need for suitable predictors during childhood and adolescence to anticipate health effects during adulthood.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The Effect of Regular Consumption of Reformulated Breads on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Schadow, Alena M.; Revheim, Ingrid; Spielau, Ulrike; Dierkes, Jutta; Schwingshackl, Lukas; Frank, Jan; Hodgson, Jonathan M.; Moreira-Rosário, André; Seal, Chris J.; Buyken, Anette; Rosendahl-Riise, Hanne (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

CausalQA: A Benchmark for Causal Question Answering - Bondarenko, Alexander; Wolska, Magdalena; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille; Stein, Benno; Braslavski, Pavel; Hagen, Matthias; Potthast, Martin (Proceedings of the 29th International Conference on Computational Linguistics)
At least 5% of questions submitted to search engines ask about cause-effect relationships in some way. To support the development of tailored approaches that can answer such questions, we construct Webis-CausalQA-22, a benchmark corpus of 1.1 million causal questions with answers. We distinguish different types of causal questions using a novel typology derived from a data-driven, manual analysis of questions from ten large question answering (QA) datasets. Using high-precision lexical rules, we extract causal questions of each type from these datasets to create our corpus. As an initial baseline, the state-of-the-art QA model UnifiedQA achieves a ROUGE-L F1 score of 0.48 on our new benchmark.

A parameterized view on the complexity of dependence and independence logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Journal of Logic and Computation)
Abstract In this paper, we investigate the parameterized complexity of model checking for Dependence and Independence logic, which are well studied logics in the area of Team Semantics. We start with a list of nine immediate parameterizations for this problem, namely the number of disjunctions (i.e. splits)/(free) variables/universal quantifiers, formula-size, the tree-width of the Gaifman graph of the input structure, the size of the universe/team and the arity of dependence atoms. We present a comprehensive picture of the parameterized complexity of model checking and obtain a division of the problem into tractable and various intractable degrees. Furthermore, we also consider the complexity of the most important variants (data and expression complexity) of the model checking problem by fixing parts of the input.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

Pulver im 3D-Druck - von Mascarabürsten bis zum Interieur eines Mini-Coopers (Vortrag) - Kletetzka, Ivo; Klippstein, Sven Helge (3D-DRUCK HAUTNAH - Der Einfluss einer Zukunftstechnologie auf unser Leben)

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

Zero-Sequence Voltage Reduces DC-Link Capacitor Demand in Cascaded H-Bridge Converters for Large-Scale Electrolyzers by 40% - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (24th European Conference on Power Electronics and Applications (EPE'22 ECCE Europe))
Cascaded H-bridge Converters (CHBs) are a promising solution in converting power from a three-phase medium voltage of 6.6 kV...30 kV to a lower DC-voltage in the range of 100 V...1 kV to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC microgrids. CHBs can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, require a large DC-link capacitor for each module to handle the second harmonic voltage ripple caused by the fluctuating input power within a fundamental grid period. Without a zero-sequence voltage injection, star-connected CHBs are operated with approximately sinusoidal arm voltages and currents. The floating star point potential enables to utilize different zero-sequence voltage injection techniques such as a third-harmonic injection with 1/6 of the grid voltage amplitude or a Min-Max voltage injection. Both well-known methods have the advantage to reduce the peak arm voltage and thereby the number of required modules by 13.4 % (to √ 3 2). This paper proves analytically that the third-harmonic injection with 1/6 of the grid voltage amplitude reduces the second harmonic voltage ripple by only 15.1 % compared to no-voltage injection for unity power factor operation and balanced grid voltages. Then it is shown, that the Min-Max injection has the often overlooked advantage of reducing the second harmonic voltage ripple by even 18.8 %. By applying the here proposed zero-sequence voltage injection in saturation modulation, the second harmonic voltage ripple of the DC-link capacitors is reduced by even 24.3 %, while still requiring the same number of modules as the Min-Max injection. For a realistic number of reserve modules, the overall energy ripple in the DC-link capacitors is reduced by 40 %.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Zero sequence voltage; Third harmonic injection; Capacitor voltage ripple

How Does Usable Security (Not) End Up in Software Products? Results From a Qualitative Interview Study - Gutfleisch, Marco; Klemmer, Jan H.; Busch, Niklas; Acar, Yasemin; Sasse, M. Angela; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

27 Years and 81 Million Opportunities Later: Investigating the Use of Email Encryption for an Entire University - Stransky, Christian; Wiese, Oliver; Roth, Volker; Acar, Yasemin; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

A Collection of Deep Learning-based Feature-Free Approaches for Characterizing Single-Objective Continuous Fitness Landscapes - Seiler, Moritz Vinzent; Prager, Raphael Patrick; Kerschke, Pascal; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference)
Exploratory Landscape Analysis is a powerful technique for numerically characterizing landscapes of single-objective continuous optimization problems. Landscape insights are crucial both for problem understanding as well as for assessing benchmark set diversity and composition. Despite the irrefutable usefulness of these features, they suffer from their own ailments and downsides. Hence, in this work we provide a collection of different approaches to characterize optimization landscapes. Similar to conventional landscape features, we require a small initial sample. However, instead of computing features based on that sample, we develop alternative representations of the original sample. These range from point clouds to 2D images and, therefore, are entirely feature-free. We demonstrate and validate our devised methods on the BBOB testbed and predict, with the help of Deep Learning, the high-level, expert-based landscape properties such as the degree of multimodality and the existence of funnel structures. The quality of our approaches is on par with methods relying on the traditional landscape features. Thereby, we provide an exciting new perspective on every research area which utilizes problem information such as problem understanding and algorithm design as well as automated algorithm configuration and selection.

Automated Algorithm Selection in Single-Objective Continuous Optimization: A Comparative Study of Deep Learning and Landscape Analysis Methods - Prager, Raphael Patrick; Seiler, Moritz Vinzent; Trautmann, Heike; Kerschke, Pascal (Parallel Problem Solving from Nature — PPSN XVII)
In recent years, feature-based automated algorithm selection using exploratory landscape analysis has demonstrated its great potential in single-objective continuous black-box optimization. However, feature computation is problem-specific and can be costly in terms of computational resources. This paper investigates feature-free approaches that rely on state-of-the-art deep learning techniques operating on either images or point clouds. We show that point-cloud-based strategies, in particular, are highly competitive and also substantially reduce the size of the required solver portfolio. Moreover, we highlight the effect and importance of cost-sensitive learning in automated algorithm selection models.

On the Potential of Automated Algorithm Configuration on Multi-Modal Multi-Objective Optimization Problems - Rook, J; Trautmann, Heike; Bossek, J; Grimme, C (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
Hardness of Multi-Objective (MO) continuous optimization problems results from an interplay of various problem characteristics, e. g. the degree of multi-modality. We present a benchmark study of classical and diversity focused optimizers on multi-modal MO problems based on automated algorithm configuration. We show the large effect of the latter and investigate the trade-off between convergence in objective space and diversity in decision space.

An Open-Source FEM Magnetic Toolbox for Calculating Electric and Thermal Behavior of Power Electronic Magnetic Components - Förster, Nikolas; Hölscher, Jonas; Piepenbrock, Till; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Professionalisierung von Lehramtsstudierenden für sprachbildenden Fachunterricht im Berufsfeld Ernährung und Hauswirtschaft - Dehn, Freya; Meyer, Anja; Niederhaus, Constanze; Schlegel-Matthies, Kirsten (HiBiFo – Haushalt in Bildung & Forschung)
Aufgrund der heterogenen Schülerschaft im Berufsfeld Ernährung und Hauswirtschaft müssen Studierende für sprachbildenden Fachunterricht professionalisiert werden. Aufbauend auf einer theoretischen Fundierung werden konkrete Umsetzungsbeispiele anhand von drei exemplarischen Online-Modulen für den Ausbildungsberuf Hotelfachfrau/-mann vorgestellt.

Batch Constrained Bayesian Optimization for UltrasonicWire Bonding Feed-forward Control Design - Hesse, Michael; Hunstig, Matthias; Timmermann, Julia; Trächtler, Ansgar (Proceedings of the 11th International Conference on Pattern Recognition Applications and Methods (ICPRAM))
Ultrasonic wire bonding is a solid-state joining process used to form electrical interconnections in micro and power electronics and batteries. A high frequency oscillation causes a metallurgical bond deformation in the contact area. Due to the numerous physical influencing factors, it is very difficult to accurately capture this process in a model. Therefore, our goal is to determine a suitable feed-forward control strategy for the bonding process even without detailed model knowledge. We propose the use of batch constrained Bayesian optimization for the control design. Hence, Bayesian optimization is precisely adapted to the application of bonding: the constraint is used to check one quality feature of the process and the use of batches leads to more efficient experiments. Our approach is suitable to determine a feed-forward control for the bonding process that provides very high quality bonds without using a physical model. We also show that the quality of the Bayesian optimization based control outperforms random search as well as manual search by a user. Using a simple prior knowledge model derived from data further improves the quality of the connection. The Bayesian optimization approach offers the possibility to perform a sensitivity analysis of the control parameters, which allows to evaluate the influence of each control parameter on the bond quality. In summary, Bayesian optimization applied to the bonding process provides an excellent opportunity to develop a feedforward control without full modeling of the underlying physical processes.
Keywords: Bayesian optimization; Wire bonding; Feed-forward control; model-free design

"They’re not that hard to mitigate": What Cryptographic Library Developers Think About Timing Attacks - Jancar, Jan; Fourné, Marcel; Braga, Daniel De Almeida; Sabt, Mohamed; Schwabe, Peter; Barthe, Gilles; Fouque, Pierre-Alain; Acar, Yasemin (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

Committed to Trust: A Qualitative Study on Security & Trust in Open Source Software Projects - Wermke, Dominik; Wöhler, Noah; Klemmer, Jan H.; Fourné, Marcel; Acar, Yasemin; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

"Desperate Times Call for Desperate Measures": User Concerns with Mobile Loan Apps in Kenya - Munyendo, Collins W.; Acar, Yasemin; Aviv, Adam J. (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

Motivate the Crowd or Crowd-Them Out? The Impact of Local Government Spending on the Voluntary Provision of a Green Public Good - Bartels, Lara; Kesternich, Martin
Keywords: General Earth and Planetary Sciences; General Environmental Science

More Money or Better Procedures? Evidence From an Energy Efficiency Assistance Program - Chlond, Bettina; Goeschl, Timo; Kesternich, Martin
Keywords: General Earth and Planetary Sciences; General Environmental Science

The Intention-Behavior Gap in Climate Change Adaptation - Kesternich, Martin; Osberghaus, Daniel; Botzen, Willem Jan Wouter
Keywords: General Earth and Planetary Sciences; General Environmental Science

Pariser Klimaschutzabkommen – Berichtsstandards und Begleitanalysen nationaler Klimaschutzbeiträge stärken - Kesternich, Martin; Will, Ulrike; Manger-Nestler, Cornelia